Utility of First Dorsal Metacarpal Artery Flap for Thumb Defects - Muhammad Ali Adnan, Sadia Rasheed, Jameeat Mal, Kashan Shaikh, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Thumb defects induced by trauma lead to significant functional disability. The goal of this study was to identify the safety, versatility, and limitations, benefits, and functional outcomes, range of motion and reestablish sensory experience. These characteristics, in addition to a secure soft tissue cover, are needed for thumb restructuring. Study design: This was a retrospective study carried out in the Plastic Surgery Department of Shaheed Mohtarma Benazir Bhutto Institute of Trauma, Karachi from November 2021 to December 2022. Methods: The total 17 participants with traumic thumb defects which insert and treated with island flaps. The participants included 5 females and 12 males, the age group was 20-50 years and the average age (36 years). All patients were evaluated for the occurrence of early post-operative complications in terms of flap necrosis. Results: The operative time was 1 hours. The 15 participants underwent island FDMA ﬂap except 2 participants which show necrosis but without again treatment recover. To evaluate the esthetic and functional outcome by Kapandji score, 2-PD, SS score and esthetic outcome follow by one year. Regarding the functional recovery Kapandji, 2-PD, the esthetic and subjective satisfactory score outcome was evaluated and show significant changes p<0.005. Conclusion: FDMA is one of the best choices for reconstituting distal thumb injuries, and it is a simple technique that has the potential to enhance the island's survival and lowering the rate of distal necrosis. The FDMA flap provides good functional results while causing little donor-site morbidity. Keywords: Cortical reorientation, Metacarpal artery, Island Flap, Two point discriminate.